Analysis of the synthetic storm technique using rain height models to predict rain attenuation in tropical regions - Lwas, Ali K.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Ismail, Ahmad Faris; Abdullah, Khaizuran; Alhareth , Zyoud; Chebil, Jalel; Singh, Mandeep (2014)
This paper aims to investigate the utilization of the Synthetic Storm Technique to convert rain rate time series to rain attenuation time series using the ITU-R P.839, Stutzman and Bryant rain height models. Furthermore, the study aims to compare the actual rain attenuation with that predicted by the SST using the three above-mentioned rain height models based on rain rate and rain attenuation both measured concurrently. The reason for conducting this study is the fact that previous studies found that SST derived attenuation using the ITU-R P.839 rain height model is close to measured attenuation in low rain intensity but it is overestimated in medium rainfall and extremely overestimated in high rainfall rate. Therefore, it is vital to investigate the utilization of the SST using two additional rain height models which are the Stutzman and Bryant models. The study relies on rain rate time series and rain attenuation time series measured at University Science Malaysia (USM) campus (4.390 N, 100.980 E). The study found that the higher the rain rate, the higher is the percentage error for the SST predicated rain attenuation using the three above-mentioned rain height models as compared with measured rain attenuation. However, it is observed that when the Stutzman model applied as part of the SST model, the prediction is more accurate of the three rain height models.